Комплексне лікування хворих на простатит з точки зору сучасних вимог - Бачурін, Георгій Вікторович; Bachurin, H. V. (My University, 2015)
Обследовано 118 больных, которые поступили в урологическую клинику по поводу простатитов. Из них у 63 был острый простатит, а у 55 больных – хронический. Наряду с общеклиническими проведены бактериологические обследованиями с целью определения микрофлоры в моче. При этом выявилось, что бактериурия положительной была у 96 больных (81,3%), и почти поровну между моно инфекцией (50 человек) и микс-инфекцией (46 человек). Кроме этого у 18 больных призведено исследование простатического сока. Выяснилось что основным источником инфекции была кишечная палочка, как моноинфекция - 20 человек (20,7%) и в составе микст-инфекции – в 25 случаях (26,1%). Второй причиной простатита были стафилоккоки эпидермальные и гемолитические, всего у 31 больного. Четко определены возможности воздействия препаратов на микрофлору. При этом превалируют ванкомицин, ликезалид, и антибиотики цефалоспоринового ряда. Для достижения стойкого успеха предлагается целый ряд фитосборов для включения их в комплексное лечение простатитов. 118 patients with prostatitis were examined in our urological clinic. 63 of them had acute prostatitis, and 55 patients – chronic prostatitis. In addition to common clinical examinations, bacteriological investigations were conducted to determine microorganisms in urine. Bacteriuria was revealed in 96 patients (81.3%), almost equally between the mono-infection (50 patients) and mixed infection (46 patients). Besides, prostatic fluid was examined in 18 patients. It was revealed that Escherichia coli was the main source of infection, and as mono-infection it was found in 20 patients (20.7%), and in the composition of mixed infections – in 25 cases (26.1%). The second causes of prostatitis were Staphylococcus epidermidis and hemolyticus in 31 patients. The opportunities of drug influence on microorganisms were clearly defined. The most effective antibiotics are vancomycin, linezolid and cephalosporin. In order to achieve the lasting success, we offer a wide range of herbal medicines to include them in comprehensive treatment of prostatitis.
Comprehensive treatment of patients with prostatitis from the viewpoint of modern requirements
Keywords: комплексное лечение; простатит; антибиотики; фитосборы; comprehensive treatment; prostatitis; antibiotics; phytotherapy